2012
DOI: 10.1111/j.1476-5381.2012.02102.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase‐4 inhibitor improves neovascularization by increasing circulating endothelial progenitor cells

Abstract: BACKGROUND AND PURPOSE Current methods used to treat critical limb ischaemia (CLI) are hampered by a lack of effective strategies, therefore, therapeutic vasculogenesis may open up a new field for the treatment of CLI. In this study we investigated the ability of the DPP‐4 inhibitor, sitagliptin, originally used as a hypoglycaemic agent, to induce vasculogenesis in vivo. EXPERIMENTAL APPROACH Sitagliptin were administered daily to C57CL/B6 mice and eGFP transgenic mouse bone marrow‐transplanted ICR mice that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 57 publications
5
65
0
3
Order By: Relevance
“…Additionally, as compared to a lower dosage of sitagliptin, the higher dosage of sitagliptin was more effective in up-regulating the EPC expression in the renal parenchyma. In this way, our study is consistent with the results of recent studies [27,[29][30][31][32] . Our finding of enhanced EPC expression in acute IR kidney injury supports the essential role of EPCs in repairing injured endothelial cells and participation in angiogenesis in response to ischemic insult from acute IR injury.…”
Section: Wwwnaturecom/apssupporting
confidence: 83%
See 2 more Smart Citations
“…Additionally, as compared to a lower dosage of sitagliptin, the higher dosage of sitagliptin was more effective in up-regulating the EPC expression in the renal parenchyma. In this way, our study is consistent with the results of recent studies [27,[29][30][31][32] . Our finding of enhanced EPC expression in acute IR kidney injury supports the essential role of EPCs in repairing injured endothelial cells and participation in angiogenesis in response to ischemic insult from acute IR injury.…”
Section: Wwwnaturecom/apssupporting
confidence: 83%
“…Interestingly, another experimental study has revealed that sitagliptin therapy enhanced neovascularization through increasing circulating number of EPCs [29] . Additionally, a clinical observational study has also shown that sitagliptin therapy increases the circulating level of EPCs in patients with type II diabetes mellitus [29,30] .…”
Section: Wwwnaturecom/apsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with sitagliptin attenuated intimal hyperplasia in response to vascular injury in rats (9), and both sitagliptin and alogliptin reduced atherosclerotic lesions in a mouse model (10,11). Alogliptin treatment was also found to modulate endotheliumdependent vasodilation in mouse aortic segments (12), and sita-gliptin augments neovascularization by increasing circulating endothelial progenitor cells in vivo (13). Treatment with sitagliptin in diabetic patients reverses vascular endothelial dysfunction as assessed by increased flow-mediated dilation and also increases circulating adiponectin levels (14).…”
mentioning
confidence: 94%
“…60 Similar findings have also been reported in experimental diabetic cardiomyopathy 44 and hindlimb ischemia. 61 The effects of DPP4 inhibition have also been examined in patients with T2DM in whom 4 weeks of treatment increased both plasma SDF-1 level and the circulating EPC (CD34 + / VEGFR2 + ) count. 62 However, whether these SDF-1-related mechanisms may also account for the diminution in cardiovascular events observed in meta-analyses of DPP-4 treatment in diabetic patients 63 remains speculative.…”
Section: Angiogenic Activitymentioning
confidence: 99%